Intellectual potential of innovation - Lysenko, A. M. (WSEH, 2024)
The report substantiates that the intellectual potential of innovation activity is a complex set of knowledge, skills, creative thinking and intellectual resources that ensure the creation, development and implementation of new ideas, technologies or products. It is a key factor in today's knowledge economy, where the competitiveness of countries and companies depends on their ability to innovate.
Інтелектуальний потенціал інноваційної діяльності
Keywords: intellectual potential; commercialization; innovation activity; technology transfer; creative thinking